2013
DOI: 10.1021/la401936w
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Shifts of the Leidenfrost Temperature from Multiscale Micro/Nanostructured Surfaces

Abstract: In the present work, the effects of surface chemistry and micro/nanostructuring on the Leidenfrost temperature are experimentally investigated. The functional surfaces were fabricated on a 304 stainless steel surface via femtosecond laser surface processing (FLSP). The droplet lifetime experimental method was employed to determine the Leidenfrost temperature for both machine-polished and textured surfaces. A precision dropper was used to control the droplet size to 4.2 μL and surface temperatures were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 43 publications
4
83
0
Order By: Relevance
“…Overall the LFP on the processed surface is higher than that of the polished surface for all droplet sizes investigated. More on the effects of microstructures and contact angle on the LFP can be found on a recently published paper by our group [16]. As for the effects of droplet size, the LFP was shown to shift 45 O C over the range of droplet sizes on the polished sample compared to 85 O C over the same range of droplet sizes on the ASG-Mounds sample.…”
Section: Leidenfrost Determinationmentioning
confidence: 87%
See 1 more Smart Citation
“…Overall the LFP on the processed surface is higher than that of the polished surface for all droplet sizes investigated. More on the effects of microstructures and contact angle on the LFP can be found on a recently published paper by our group [16]. As for the effects of droplet size, the LFP was shown to shift 45 O C over the range of droplet sizes on the polished sample compared to 85 O C over the same range of droplet sizes on the ASG-Mounds sample.…”
Section: Leidenfrost Determinationmentioning
confidence: 87%
“…A more recent publication by Kruse et al [16], details large shifts in the Leidenfrost temperature on stainless steel via enhanced micro/nanoscale surface roughness. Using Femtosecond Laser Surface Processing (FLSP) techniques to produce superhydrophillic stainless steel surfaces, the LFP was increased from 280 to 455 O C. While others have used coatings, or applied external materials to a surface to change the surface features, our approach does not require the addition of any outside materials.…”
Section: Introductionmentioning
confidence: 99%
“…Heat flux is measured via embedded thermocouples and surface temperature is calculated. A more in depth description of the FLSP technique and the pool boiling experimental setup is given by Kruse et al 24,26 Five unique surfaces are analyzed in this work, two Inconel, two stainless steel, and one copper. Their surface characteristics have been obtained using a Keyence Laser Confocal Microscope and are tabulated in Table I.…”
mentioning
confidence: 99%
“…The reported values of the Leidenfrost temperature on a flat silicon surface ranges from 200 to 390°C 9,[14][15][16][17][18] . Although the majority of the studies on textured surfaces report a relative increase in the Leidenfrost temperature 10,14,[18][19][20][21][22] , a few recent studies reported a significant decrease in the Leidenfrost temperature on microstructured hydrophobic surfaces [23][24][25][26] . For example, del Cerro et al 23 observed suspended droplets on heated surfaces composed of hydrophobic micropillars and microholes at temperatures 70% lower than the Leidenfrost point on a smooth surface.…”
mentioning
confidence: 99%